Técnicas para obtener una armoniosa convivencia escolar en los niños y niñas de segundo grado de educación básica de la escuela fiscal mixta República de Cuba, del barrio Payanchi, de la ciudad de Loja. año lectivo 2013 – 2014 - Armijos Serrano, Verónica Lizeth (2015)
This research entitled: TECHNIQUES FOR A HARMONIOUS LIVING TOGETHER IN SCHOOL CHILDREN OF SECOND DEGREE OF BASIC EDUCATION SCHOOL TAX MIXED "REPUBLIC OF CUBA" DEL BARRIO PAYANCHI, CITY OF LOJA. SCHOOL YEAR 2013 - 2014, for which he worked with the following general objective: to help improve the harmonious school life of children in second grade of Basic Education, which served to initiate the investigation, with a design Quasi-experimental, but the comprehensive, analytic, synthetic, models or methods proactive and comprehensive evaluation workshop that allowed knowing the impact of the application of techniques for working in the classroom; from the use of a survey and a knowledge test aimed to five students and a teacher were used to know the reality of the problem by applying a workshop of appropriate and varied techniques for work where I conclude that the positive impact is evident in achieving a harmonious school life.